Assessment of thermodynamic perfection of working substancesin cascade refrigerators - Морозюк, Лариса Ивановна (Eastern-European Journal of Enterprise Technologies, 2015)
Cascade compressor refrigerators maintain the cooled object temperature at the level of –110 oC to –50 oC. Their complex cycle consists of sequentially aligned single-stage cascade cycles with various working substances and mass flows. Cascade refrigerators at a high temperature upper stage (US) mainly worked on such substances as R12 and R22, whereas R13 and R14 were used at a lower stage (LS). According to the Regulations of International Protocols and Agreements on environmental safety of refrigerating machines, the above mentioned working substances are banned, which has resulted in the search of new pairs of working substances that would meet the requirements of both energy saving and environment safety. The study considers a technique for selecting a pair of working substances for cascade machines at the first stage of entropy-cyclic method of thermodynamic analysis, i.e. determining the rate of thermodynamic perfection of the actual complex cycle. Three working substances—R744, R717, and R290—in different combinations within cycles-stages, have been used to compare thermodynamic perfection of pairs and shown a mutual impact of working substance properties on the machine perfection as a whole.